Rancang Bangun Alat Parut Modifikasi sebagai Teknologi Tepat Guna - Ovilia putri utami gumay; Reno Ali Afan (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2023)
Coconut meat is one type of raw material that is most often used in the small food catering industry, where coconut processing is done by grating it. The process of grating coconut is sufficient to be done manually with a simple grater board if there are only a few, to produce a good grater, the speed of a manual grater requires approximately 3000 grating movements every hour. A coconut grater is a tool product for household needs that functions as a tool to crush coconuts into small granules, with the aim of obtaining the coconut milk contained in the coconut flesh. This study aims to design an appropriate technology in the form of a more ergonomic mid-scale modified coconut grater. From the test results obtained, the higher the rotational speed of the cylinder or the cutting speed of the grating knife, the higher the grating capacity. This is because the faster the cutting speed of the grating knife, the faster the cycle or frequency of grating.